The Accountant's Guide to Legal Liability and Ethics. - Ward, D. Dewey (The Accounting Review, 1994)
Abstract Reviews the book `The Accountant's Guide to Legal Liability and Ethics,' by Mark J. Epstein and Albert D. Spalding, Jr.